O kierunkach rozwoju prawa karnego na ziemiach polskich w dobie średniowiecza wobec tradycji i tendencji europejskich - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The publication is an attempt to look at the history of law in Poland from the perspective of the development of European legal culture. The choice of the subject matter to be explored determined the author’s methodological instruments, ultimately prompting him to consider comparative legal studies as the basis for his research. At the outset, emphasizing the topicality of the problem in the context of the progress of European integration, the author strove to present the history of criminal law in medieval Poland, highlighting both the original developmental features and the way in which they fit into universal tendencies, represented in the legal systems of other contemporary countries of the Old Continent. In his final conclusions, he drew attention to the tendencies that emerged at the end of the Middle Ages and at the beginning of the modern era, pointing to the growing discrepancies in the directions of further development of law in Polish lands against the tendencies that began to dominate more and more clearly in the laws of most European countries at that time. The author’s intention was not to discover America a few hundred years after Columbus, but to synthesize a multifaceted problem that could serve historical-legal reflection.
Keywords: history of law; judicial law; criminal law; comparative legal studies; legal culture; Rechtsgeschichte; Gerichtsrecht; juristische Komparatistik; Rechtskultur